Impact of emergent technologies on US workforce: exploratory analysis. - Toskin, Katarzyna (Journal of Information Systems Applied Research, 2023)
Keywords: dept.bis; peer-reviewed; ⛔ No DOI found

Teaching tip GetVirtual: A universal service-based learning framework - Toskin, K.; Pisano, M.A.; Corey, T. (Journal of Information Systems Education, 2023)
This paper introduces a universal framework for service-based learning which provides information systems students with opportunities to gain invaluable hands-on experience. More specifically, through this framework, students can develop hard, soft, and interdisciplinary skills in preparation for their first professional careers upon graduation. In addition to introducing the framework, we provide student testimonials and feedback as well as lessons learned from our experience in efforts to prepare and help other schools interested in offering similar growth opportunities to their students to have a smooth and successful implementation. © 2023, Journal of Information Systems Education. All Rights Reserved.
Keywords: Experiential learning & education; Framework; GetVirtual; Service-learning; Teaching tip; dept.bis; peer-reviewed; ⛔ No DOI found